Effect of IL-28 B Polymorphisms on Early Virological Response (EVR) in Chronic Hepatitis C Patients Treated with Interferon and Ribavirin - Madeeha Nazar,Madiha Ehtesham , Abrar Akbar , Muhammad Umar ,Faiza Aslam ,Arslan Shahzad ,Tayyab Saeed Akhter , Gul Nisar ,Aqsa Naseer ,Sadia Ahmed (Journal of Rawalpindi Medical College, 2016)
Background: To determine the frequency of EVR in chronic hepatitis C (CHC) patients treated with Interferon and Ribavirin and to compare the effect of IL-28B SNP rs12979860 (CC and non CC genotypes) on frequency of EVR. Methods: In this cross-sectional study 100 patients with Chronic Hepatitis C (CHC) with genotype 3 who received Interferon and Ribavirin in the standard doses were categorized in two groups depending upon the IL-28B SNP rs12979860 CC and non CC genotypes. Results of Qualitative PCR for HCV RNA after 12 weeks of treatment and EVR were entered. Frequency of EVR in the two groups (CC and non CC) was compared. Results: Among the 100 patients with Chronic Hepatitis C treated with Interferon and Ribavirin, 72 patients achieved EVR (72%). Out of the 100 patients, 52 had CC genotype and 48 had non-CC genotype (40 with CT and 8 with TT genotype). In the CC group 47 out of 52 patients achieved EVR (90%) while in the non-CC group 25 out of 48 patients achieved EVR (52%). The p value in our study was 0.00 Conclusion: The frequency of EVR is 72% in Chronic Hepatitis C patients infected with genotype 3 treated with Interferon and Ribavirin which is comparable with Pegylated Interferon and Ribavirin. Patients with IL-28B SNP rs12979860 CC genotype have a better chance to achieve EVR (90%) as compared to the non-CC genotype (52%).